2021
DOI: 10.1101/2021.02.11.430703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

REAP: A platform to identify autoantibodies that target the human exoproteome

Abstract: Autoantibodies that recognize extracellular protein epitopes (the "exoproteome") exert potent functional effects that underlie numerous disease processes. Identifying these antibodies can thus provide insights into the pathophysiology of a wide spectrum of illnesses and therapeutic strategies to treat them. Here, we developed Rapid Extracellular Antigen Profiling (REAP) as a technique for comprehensive and high-throughput discovery of exoproteome-targeting autoantibodies. With REAP, patient samples are applied… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Anyhow, the results of our work underscores recent studies 3,6,10,12 that report the generation of autoantibodies following SARS-CoV-2 infection. Importantly, our data indicate that an additional immunological layer is present where autoantibodies targeting GPCRs and RASrelated molecules are associated with COVID-19 burden.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Anyhow, the results of our work underscores recent studies 3,6,10,12 that report the generation of autoantibodies following SARS-CoV-2 infection. Importantly, our data indicate that an additional immunological layer is present where autoantibodies targeting GPCRs and RASrelated molecules are associated with COVID-19 burden.…”
Section: Discussionsupporting
confidence: 84%
“…Anyhow, the results of our work underscores recent studies 3,6,10,12 The Random Forest model revealed the interaction between autoantibodies targeting CXCR3 and AT1R as the most important predictors of COVID-19 severity. There is an essential biological connection between CXCR3 and AT1R.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In APECED patients, the detection of several tissue antigen-directed autoantibodies has been associated with the presence of corresponding organ-specific autoimmune manifestations (13,52,(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75). New experimental approaches such as phage/bacterial peptide display (PhiP-Seq) and yeast surface display (REAP) have been recently used to uncover novel autoantigen specificities such as KHDC3L, associated with primary ovarian failure, RFX6, associated with intestinal dysfunction, and colipase, associated with exocrine pancreatic insufficiency (76,77). However, for most of the tissue antigentargeted autoantibodies detected in APECED patients, it is difficult to reliably predict the development of the corresponding autoimmune manifestation at the individual patient level as their sensitivity and specificity is not very high.…”
Section: Tissue Antigen-specific Autoantibodiesmentioning
confidence: 99%
“…Similarly, membrane associated antigens may be misfolded or under-represented on both of the array platforms utilised given the uniform approach required to express and purify such large numbers of antigens in parallel. To overcome this limitation, and expand the antigen space examined in the context of ARF, alternative approaches such as Phage Immunoprecipitation Sequencing [PhiP −Seq (53)] and Rapid Extracellular Antigen Profiling [REAP (54)] of the human proteome could be considered in future studies. Finally, the initial array analysis was based on small patient numbers and it is possible that additional ARF autoantibodies would be detected with larger cohorts.…”
Section: Discussionmentioning
confidence: 99%